The Perspective of Plato Concerning the Position of Love in Philosophy Analysis of The Symposiu - Muhammad Irfan Syaebani; Untung Yuwono; Embun Kenyowati Ekosiwi (Jurnal Filsafat Indonesia, 2023)
Plato was the first philosopher who discussed love philosophically. The discussion can be found in his work entitled Symposium. Through text analysis of Symposium, the perspective of Plato about love and the position of love in philosophical discourse can be concluded. For Plato, ultimate love does not have a relation to the body anymore. Plato believed that love is hierarchical, and it ascends from the lower level to the higher level as illustrates in Scala Amoris. The ultimate love is about a mental state which aims to gain absolute beauty and it is the highest level of love. However, in romantic relationships, love is not only about the mental state but also physical contact because romantic love relates to sexual things such as sexual intimacy. And according to Plato, love that still has attachment to the body is the lowest level of love. Thus, Plato's perspective about romantic love cannot be said as positive because romantic love strongly relates to the body. Plato believed that the highest level of love has left body behind, and it only focuses on mental aspiration.